Food Packaging Innovation to Extend Shelf Life and Reduce Food Waste in a Leading Company in Indonesia - Dewi, Irra Chrisyanti; Megavitry, Rissa; Auliani, Restu; Manik, Erba Kalto (Westscience Press, 2023)
This research investigates the impact of food packaging innovations on shelf life extension and food waste reduction within a leading Indonesian food company. Employing a quantitative approach, the study incorporates a diverse sample of products subjected to various packaging technologies. Descriptive and inferential statistics reveal a statistically significant increase in shelf life by 50% and a substantial reduction in food waste by 40%. Consumer surveys underscore positive perceptions, with 80% expressing a preference for sustainable packaging. Economically, a 15% reduction in costs associated with product losses supports the business case for innovative packaging. These findings contribute empirical evidence to the discourse on sustainable food systems, emphasizing the practical effectiveness and economic viability of advanced packaging technologies.